GROSS PROFIT ANALYSIS OF RICE SEED SALES PT. FARMERS (PERSERO) SPB KEDIRI IN WEST LOMBOK - Massuki Fitri, Syarifah; Pahmi, Saepul (Jurnal Ilmiah Ilmu Manajemen, 2020)
This study aims to determine the factors that influence changes in gross profit of rice seed sales at PT. Pertani (Persero) SPB Kediri, West Lombok. The type of research used in this research is descriptive quantitative. Data collection techniques used in this study were interviews and documentation. Based on the calculation results, it can be concluded that the factors that affect changes in gross profit are sales factors, selling price changes, production quantity changes, changes in the cost of goods sold per unit product, and changes in the quantity of cost of goods sold due to changes in the quantity produced. sold or produced and changes in gross profit vary, predominantly due to changes in the cost of goods sold.